[OP.4D.06] REDUCTION OF CORTICAL OXYGENATION IN CHRONIC KIDNEY DISEASE: EVIDENCE OBTAINED WITH BOLD-MRI AND A NEW ANALYTIC TECHNIQUE. (September 2016) - Milani, B.; Ansaloni, A.; Sousa-Guimaraes, S.; Piskunowicz, M.; Vogt, B.; Stuber, M.; Burnier, M.; Pruijm, M.
Abstract : Objective: The determination of renal tissue oxygenation by BOLD-MRI in chronic kidney disease (CKD) patients has given heterogeneous results, possibly due to the lack of a widely accepted procedure to analyze the R2* maps. We present a new technique for the analysis of renal BOLD-MRI called the twelve-layer concentric objects method (TLCO). We measured its reproducibility and assessed whether differences in the intra-renal distribution of R2* as a measure of oxygenation were detected between CKD patients and controls. Figure. No caption available. Design and method: MR imaging (3 Tesla) was performed under standardized conditions before and 15 min after furosemide injection in 104 CKD patients, 61 hypertensive patients and 42 healthy volunteers. MR images were analyzed with the TLCO technique that divides renal parenchyma in 12 equal layers (see figure). Mean R2* value of each layer was reported, as well as the steepness of the slope of the R2* curve linking the mean R2* from the 3rd to the 7th layer. In a subgroup of 52 individuals (20 controls, 18 moderate CKD, 14 severe CKD) each exam was analyzed by two different observers to assess inter-observer variability. Results: Inter-observer variability was respectively 2.3 ± 0.9%, 1.9 ± 0.8% and 3.0 ± 2.3% in controls, mild to moderate and severe CKD. Mean R2* of the outer (more cortical) layers was significantly higher in CKD suggesting a lower cortical oxygenation. The response to furosemide was smaller in the inner (more medullary) layers, and the R2*slope was flatter in CKD patients than in healthy and hypertensive controls. In multivariable regression analysis, the slope of the R2* profile correlated positively with eGFR in patients with an eGFR < 90 ml/min/1.73m 2 (p < 0.001). Conclusions: Our data confirm the hypothesis that renal cortical oxygenation is reduced in CKD and show in humans that the level of cortical oxygenation correlates with the severity of chronic kidney disease. The TLCO-technique is highly reproducible and provides layer-by-layer information on renal R2* values from the cortex to the medulla. Analysis of the slope factor offers information on the intra-renal distribution of R2*, and as such represents a measure of cortico-medullary differentiation.